Not all oil types are alike - Jochen Güntner; Michael Irlacher; Peter Öhlinger (Johannes Kepler University of Linz, Department of Economics, 2023)
Motivated by the European Union's debate on sanctioning crude oil imports from Russia, we estimate the elasticity of substitution between different crude oil types. Using European data on country-level crude oil imports by field of origin, we argue that crude oil is not a homogenous good and that the relevant substitutability for analyzing the impact of trade sanctions must account for the quality of different oil types in terms of their API gravity and sulfur content. Our results suggest that, by neglecting these differences in quality, standard estimates significantly underestimate the production disruptions in crude oil refining resulting from sanctions.
Keywords: 330